2010
DOI: 10.1007/s00531-010-0551-0
|View full text |Cite
|
Sign up to set email alerts
|

Can shells of freshwater mussels (Unionidae) be used to estimate low summer discharge of rivers and associated droughts?

Abstract: 18 O ar values were measured in the aragonite of the growth increments of four Unio sp. shells; two from a relatively wet period and two from a very dry time interval (1910-1918 and 1969-1977, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…marine: Romanek et al, 1987;Kennedy et al, 2001;Schone et al, 2003;Chauvaud et al, 2005;Freitas et al, 2005;Schone et al, 2005;Thebault et al, 2007; estuarine: Goodwin et al, 2001;Dettman et al, 2004;Schone et al, 2004a;Gillikin et al, 2005;freshwater: Dettman et al, 1999;Schone et al, 2004b;Versteegh et al, 2011). The wide geographic distribution of bivalve species adds to their value as climate archives, as many can provide records from regions where other biogenic carbonates that can provide paleoenviromental proxies, such as corals, are not available.…”
Section: Introductionmentioning
confidence: 99%
“…marine: Romanek et al, 1987;Kennedy et al, 2001;Schone et al, 2003;Chauvaud et al, 2005;Freitas et al, 2005;Schone et al, 2005;Thebault et al, 2007; estuarine: Goodwin et al, 2001;Dettman et al, 2004;Schone et al, 2004a;Gillikin et al, 2005;freshwater: Dettman et al, 1999;Schone et al, 2004b;Versteegh et al, 2011). The wide geographic distribution of bivalve species adds to their value as climate archives, as many can provide records from regions where other biogenic carbonates that can provide paleoenviromental proxies, such as corals, are not available.…”
Section: Introductionmentioning
confidence: 99%
“…corals (Swart, 1983;Watanabe et al, 2011), coralline algae (Halfar et al, 2008;Williams et al, 2011), land snails (Goodfriend and Ellis, 2002;Yanes et al, 2011), freshwater snails (Abell and Hoelzmann, 2000;Stevens et al, 2012), freshwater bivalves (Kaandorp et al, 2003;Versteegh et al, 2010bVersteegh et al, , 2011 and marine bivalves (Jones and Quitmyer, 1996;Santos et al, 2012;Schöne et al, 2005). The oxygen isotope composition (δ 18 O values) of marine bivalves is often used as a proxy for temperature (Carré et al, 2005;Wanamaker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that through the relationship between discharge and δ 18 O w values in the Meuse, unionid δ 18 O ar records reveal the occurrence of past low-discharge summers (Versteegh et al, 2010). Ricken et al (2003) We present δ 18 O ar records of unionid shells that lived under different climate regimes and associated river conditions during the late Holocene (see next paragraph).…”
Section: Introductionmentioning
confidence: 75%